Concordance in prediction body composition of university students between different methods of evaluation - de Mello, Maicon Faccioni (2016)
The aim this study was to evaluate the concordance between bioimpedance, perimetry and skinfold thickness. Twenty five students of physical education with an average of 23.46 ± 3.67 years old, BMI 25.58 ± 3,15kg/m², height 171.9 ± 7,25cm and total body mass 72.93 ± 11,17kg participated in the study . To estimate of the body fat percentage were measured by bioimpedance (BIA), skinfold thickness (Guedes andGuedes, 1991) and perimetry. To compare the different methods were carried out analysis of variance (ANOVA), the association was determined by Pearson correlation and the concordance by Bland-Altman method with significance level of p<0.05. Thevariance analysisdid not identifysignificant differences (p>0.05). The correlation between three methods was good (between 0.76 and 0.86). However, the Bland-Altman method, was evidenced a significant difference between bioimpedance x perimetry and perimetry x skinfold thickness (p < 0.001), wich didn’t occur with bioimpedance x skinfold thickness (p > 0.05). The perimetry tended to overestimate the body fat percentage in relation to other two methods. There was a significant concordance between bioimpedance and skinfold thickness with a wide range of limits of concordance (-6.80 to 4.88%). We concluded that bioimpedande and skinfold thickness methods present concordance and the perimetry overestimates the body fat percentage in students of physical education.